Development of Project-Based Learning Instructional Materials Integrating Bojonegoro’s Jamu Gepyok Local Wisdom to Enhance Students’ Creative Thinking Skills - Sugiati, Iis; Nur Kuswanti; Novita Kartika Indah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop Project-Based Learning (PjBL) instructional materials integrated with the local wisdom of Bojonegoro’s jamu gepyok that are valid, practical, and effective in improving students’ creative thinking skills. The instructional materials consisted of a learning module, student worksheets, and a textbook. The study employed a Research and Development (R&D) approach using the 4D model, which comprises four stages: define, design, develop, and disseminate. The participants were 20 tenth-grade students at SMAN 1 Baureno. The research instruments included validation sheets, pretest and posttest assessment sheets for measuring creative thinking skills, and student response questionnaires. Data were analyzed using descriptive and inferential quantitative methods. The results showed that the instructional materials achieved a mean validity score of 3.97 out of 4.00, indicating a very high level of validity. The materials were also considered highly practical, as reflected in the Fry Graph readability results, which indicated suitability for Grade 10, and the mean student response score of 3.61 out of 4.00. Their effectiveness was demonstrated by an N-Gain score of 0.71, categorized as high, and a paired-samples t-test showing a statistically significant improvement in students’ creative thinking skills, t(19) = −15.32, p < .001. Students also expressed positive responses to the implementation of the instructional materials, with a mean response score of 3.65 out of 4.00. These findings indicate that PjBL instructional materials integrated with the local wisdom of Bojonegoro’s jamu gepyok can effectively support the development of students’ creative thinking skills. The local wisdom of *jamu gepyok* provides an authentic problem context for PjBL by enabling students to investigate local biological resources, identify problems related to the preservation and utilization of traditional knowledge, generate alternative product ideas, design and test solutions, and communicate their products or findings. These activities align with key dimensions of creative thinking, particularly fluency, flexibility, originality, and elaboration.